Pollution et risque alimentaire dans les jardins partagés franciliens - Laurence Baudelet (Revue d'ethnoécologie)
The return of horticultural production in French cities is accompanied by a growing concern about the health quality of food plants. The consumption of crops by gardeners, far from insignificant, draws attention because of the supposed or actual presence of pollutants in soil, water and air. Burying one’s head in the sand is no longer on the agenda. On the contrary, municipalities tend to systematically apply the precautionary principle. The main focus is nowadays on polluted soils and off-ground cultivation solutions constitute the most common answer to address pollution issues, even if the atmospheric context remains critical. Meanwhile phytoremediation has little success. Yet, wouldn’t it be a longer-term solution, preserving non-artificialised land and offering valuable urban carbon sink when climate change is at stake.